Cost-Effective Filtrating Suction to Evacuate Surgical Smoke in Laparoscopic and Robotic Surgery During the COVID-19 Pandemic. Issue 5 (October 2020) - Ouzzane, Adil; Colin, Pierre
Abstract : The wide and fast spread of COVID-19 around the world has led to a dramatic increase in the need for protection products both for carers and for populations. Surgical team protection includes a systematic screening of patients, wearing protection devices by all the operating staff, and adequate management of aerosols. The risk of aerosol dispersal is particularly high during laparoscopic and robotic surgeries due to the interaction between circulating CO2 and surgical smoke that may contain small viral particles. To decrease the risk of virus transmission, many recommendations have been implemented including the use of integrated insufflation devices comprising smoke evacuation and filtration mode. Such devices are lacking in many centers around the world and to overcome this urgent unmet need, we designed a cost-effective filtrating suction as a more readily available alternative.